Effects of packaging atmospheres and injection enhancement on beef postmortem proteolysis, instrumental tenderness, sensory traits, and display color - Grobbel, Jeannine Patricia (Kansas State University, 2007)
The objectives were to determine the effects of packaging and injection-enhancement on beef sensory attributes, postmortem proteolysis, and color. Muscles from USDA Select, A-maturity carcasses were fabricated into 2.54-cm steaks on d 7 postmortem. In Experiment 1, longissimus lumborum (n=14 pairs) muscles were used. Packaging treatments were: vacuum packaging (VP); 80% O2/20% CO2 (HiO2); 0.4% CO/35% CO2/64.6%N2 (ULO2CO); 0.4% CO/99.6% CO2; 0.4% CO/99.6% N2; or 0.4% CO/99.6% Ar. In Experiment 2, longissimus lumborum (n=12 pairs); semitendinosus (n=12 pairs); and triceps brachii (n=24 pairs) muscles from one carcass side were injection-enhanced or non-enhanced. Steaks were packaged into VP, HiO2, or ULO2CO MAP. Steaks packaged in HiO2 MAP were in dark storage (2°C) for 4 d and all other steaks for 14 d. Steaks were displayed under fluorescent lighting for 7 d. Trained color panelists assigned color scores. Steaks for tenderness, cooked color, and sensory were cooked to 70°C. Steaks packaged in VP or ULO2 with CO MAP had little or no discoloration. Steaks packaged in HiO2 MAP discolored faster (P < 0.05) and more (P < 0.05) than steaks in other packaging treatments. Steaks packaged in HiO2 MAP were less tender (P < 0.05) than other treatments at the end of display, but had 10 d less aging due to shorter dark storage. Steaks packaged in HiO2 had the lowest (P < 0.05) a* values for internal cooked color of all treatments and exhibited premature browning. Enhanced steaks were more tender (P < 0.05) than non-enhanced steaks. Sensory panelists found that non-enhanced steaks packaged in ULO2CO MAP or VP were more tender (P < 0.05), had more (P < 0.05) beef flavor, and had less (P < 0.05) off-flavors than steaks packaged in HiO2 MAP. Off-flavors for steaks packaged in HiO2 MAP often were described as oxidative and rancid. Enhanced steaks had more (P < 0.05) off-flavors than non-enhanced steaks. Postmortem proteolysis measured by desmin degradation was not affected (P > 0.05) by packaging. Steaks packaged in ULO2 plus CO MAP had superior color stability, tenderness, and sensory attributes compared to steaks in HiO2 MAP.
Keywords: Beef; Modified Atmosphere Packaging; Color; Sensory Traits; Postmortem Proteolysis; Injection Enhancement; Agriculture, Food Science and Technology (0359)